The impact of inflammatory factors on patients with concurrent lung cancer and acute pulmonary embolism - Li, Meizhi; Yi, Qiong; Wu, Shangjie; Li, Yuan; Li, Fang (Frontiers in Cardiovascular Medicine, 2025)
IntroductionLung cancer is a leading cause of cancer-related mortality globally, with acute pulmonary embolism (APE) significantly worsening the prognosis of affected patients. Inflammatory pathways are increasingly recognized for their dual role in both oncogenesis and thrombotic events. This study aimed to investigate the prognostic significance of specific inflammatory biomarkers, particularly neutrophil-mediated mechanisms, in lung cancer patients complicated by APE.MethodsA retrospective cohort analysis was conducted on 90 lung cancer patients admitted to the Second Xiangya Hospital of Central South University between January 2019 and December 2022. Propensity score matching (PSM) was employed to ensure balanced demographic and clinical covariates. Multivariate logistic regression analyses were performed to identify independent predictors of APE occurrence and disease severity.ResultsMultivariate logistic regression identified elevated neutrophil count as an independent predictor of APE occurrence (adjusted OR = 3.068, 95% CI: 1.472–6.394, p = 0.003). In the subgroup analysis of APE patients, hyperuricemia (UA >260.1 μmol/L; OR = 1.017, 95% CI: 1.002–1.033, p = 0.028) and a reduced platelet-to-lymphocyte ratio (PLR < 318.83; OR = 0.990, 95% CI: 0.981–0.999, p = 0.037) were significantly associated with increased disease severity and ICU admission. Receiver operating characteristic (ROC) curve analysis validated the strong discriminative capacity of neutrophil count (AUC = 0.952), UA (AUC = 0.782), and PLR (AUC = 0.792) in stratifying APE risk and clinical outcomes.DiscussionOur findings highlight neutrophilia as a potential biomarker for APE susceptibility in lung cancer patients. Furthermore, elevated uric acid levels and a diminished PLR may serve as valuable indicators of disease severity in this high-risk population. The study underscores the critical need to integrate these inflammatory markers into standardized clinical risk assessment frameworks to optimize therapeutic strategies and improve patient management.